Exploration of the correlation between welding flaw geometrical parameters and floating potential based on an ultrasonic duplex finite element model. (1st January 2021) - He, Deqiang; Chen, Jiyong; Chen, Yanjun; Miao, Jian; Deng, Jianxin; Chen, Jiqing; Liu, Jianren
Highlights: An ultrasonic duplex model was developed for flaw detection in long butt-weld. Floating potential can be used to parse several geometrical parameters of flaw. Global energy vanishing time of flaw position exhibited an upward spiral. Flaw length effects the peak number of floating potential upper envelope curve. The energy decay rate increases with increasing flaw orientation angle. Abstract: Non-destructive testing (NDT), as an indispensable technique for assessing welding quality, is expected to continuously improve. In this study, to obtain welding flaw geometrical parameters more simply and conveniently, their correlations with floating potential were explored using groups of simulation experiments. All the simulation experiments were performed with a well-designed duplex finite element model, which can simulate ultrasonic guided wave testing (UGWT) of flaws embedded in the metro traction beam butt weld. Experimental results proved that different geometrical parameters of welding flaws exhibited different traits on floating potential. Position, length and orientation parameters of flaw related individually to the energy vanishing point, the number of peaks, the travelling time between peaks, the energy decay rate and so on. Thus, recording the floating potential of the entire UGWT process shows great promise in elucidating flaw geometrical parameter information and makes the proposed approach possible for practical use.